2013
DOI: 10.5146/tjpath.2013.01174
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue giant cell tumor of low malignant potential of the neck: a case report and review of the literature

Abstract: Giant cell tumor of soft parts is a rare tumor that is clinically and histologically similar to giant cell tumor of the bone. We present a 53-year-old female with a giant cell tumor of low malignant potential arising from the neck. The clinicopathological features and the importance of immunohistochemistry in the differential diagnosis with other giant cell rich tumors was discussed. Key Words: Soft tissue neoplasms, Giant cell tumors, Head and neck neoplasms ÖZYumuşak dokunun dev hücreli tümörü, kemiğin dev h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…In our study, we used a conventional MRI and DWI approach to investigate two cases of soft tissue giant cell tumor in the limb. The radiologic abnormalities of all lesions were limited to soft tissue without obvious calcification or bone erosion, which are frequently observed at the periphery of the GCT-ST tumors [2][3][4][5][6][7] . In addition, all lesions on MRI presented with solid masses, and blurry boundaries on the upper and lower edges.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our study, we used a conventional MRI and DWI approach to investigate two cases of soft tissue giant cell tumor in the limb. The radiologic abnormalities of all lesions were limited to soft tissue without obvious calcification or bone erosion, which are frequently observed at the periphery of the GCT-ST tumors [2][3][4][5][6][7] . In addition, all lesions on MRI presented with solid masses, and blurry boundaries on the upper and lower edges.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, all lesions were significantly big (maximum lesion size ranged from 4.0 cm to 6.0cm) and were located in the superficial areas of extremities or trunk. This type of lesion is commonly observed in GCT-ST, but it can also be found in the deep soft tissues of head, neck and retroperitomeum region [2][3][4][5][6][7][8][9][10] . Unlike deep-seated masses, size criteria (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Histologically, GCT-ST lesions bear a close resemblance to their bony counterparts, giant cell tumor of bone. Most of the existing reports are pathological and clinical studies, while the imaging aspects have only been reported in the cases of adjacent bone or with atypical cystic degeneration [2][3][4][5][6][7][8][9][10][11] . With regard to MR or ultrasonography imaging features, superficial masses can be further identified based on facial edema, skin thickening, skin contact, internal hemorrhage or necrosis and lobulation of the mass [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%